“Temporary Kings”; The Metropolitan novel series and the post-War consensus - Mackay, M (Johns Hopkins University Press, 2021)
Focusing on Anthony Powell’s A Dance to the Music of Time and C. P. Snow’s Strangers and Brothers, this essay discusses the representation of parliamentary politics in the long English novel series of the postwar settlement. It demonstrates how, through the openness to contingency built into its extended historical span, the then-popular novel sequence presented a formally distinctive opportunity to imagine political consensus and continuity in an age of marked national transformation.